Prácticas alimentarias, conocimientos y suplementación en gestantes usuarias de la Clínica Hospital Municipal “Julia Esther González Delgado”, Loja - Cuenca González., Ana Cristina (2024)
Nutrition in pregnant women is a challenge of interest, since during pregnancy there is an increase in metabolic expenditure and energy requirements, so that the supply of nutrients must be adequate in quantity, quality and distribution, to ensure an adequate embryogenesis process and fetal development. Within this framework, the present study was proposed with the objective of determining the dietary practices, knowledge and supplementation in pregnant users of the Clínica Hospital Municipal “Julia Esther González Delgado - Loja, during the period October 2022 to March 2023. The study was a cross-sectional descriptive quantitative study, with a sample of 107 pregnant women. The results showed that 96.26% had more than three meals a day, 44.86% used unhealthy fats and 14.02% used a lot of salt in the preparation of food; 53.27% had an inadequate daily intake of water, 52.34% consumed junk food on a daily basis. 96.26% have a deficient consumption of carbohydrates, 57.95% of proteins and 85.09% of healthy fats. In 88.79% the intake of foods rich in calcium is insufficient, while 45.79%, 36.45% and 28.97% do not consume food sources of iron, folic acid and vitamin D or omega 3, respectively. As for supplementation, 26.17% were supplemented in the preconception stage and 94.39% in pregnancy, being in both cases iron, folic acid and calcium the most used supplements. It is concluded that most pregnant women have inadequate nutritional practices, and their knowledge regarding nutrition during pregnancy is low, however, they are adequately supplemented, so it is considered essential to provide support and nutritional care to this population